Financialisation and labour in the Australian commercial construction industry. (December 2017) - Bryan, Dick; Rafferty, Michael; Toner, Phillip; Wright, Sally
Financialisation and financial risk have become current buzzwords, but the connections between finance and labour are not well developed. Often labour is cast simply as the distributional victim of developments like shareholder value, the privatisation of public infrastructure and labour market reform. This article engages developments in the construction industry and locates a growing financial logic inside 'production' and work in that sector. Through the concepts of liquidity and risk, we identify causal connections, not just parallels, between financial innovation and the reorganisation of the logic and structure of work in the Australian construction and property services industry.